Generalized Chebyshev Highpass Filter Based On Suspended Stripline Structure (SSS) For Wideband Applications - Zakaria, Zahriladha; Mutalib, Mohamad Ariffin; Mohamad Isa, Mohd Sa'ari; Abdul Latiff, Anas; Zainuddin, Nur Aishah; Sam, Weng Yik (Penerbit UTM Press, 2014)
-